2014
DOI: 10.4161/23723548.2014.970489
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of mTOR regulation by stress

Abstract: Tumors are prime examples of cell growth in unfavorable environments that elicit cellular stress. The high metabolic demand and insufficient vascularization of tumors cause a deficiency of oxygen and nutrients. Oncogenic mutations map to signaling events via mammalian target of rapamycin (mTOR), metabolic pathways, and mitochondrial function. These alterations have been linked with cellular stresses, in particular endoplasmic reticulum (ER) stress, hypoxia, and oxidative stress. Yet tumors survive these challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 247 publications
(197 reference statements)
1
93
0
Order By: Relevance
“…It was reported that there is a crosstalk between ER stress and mTOR signaling in diverse cell types [19, 20]. Firstly, we detected increase of phosphorylated mTOR at Ser2448, not Ser2481 in HG-treated cells compared to NG and MN control (Fig.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…It was reported that there is a crosstalk between ER stress and mTOR signaling in diverse cell types [19, 20]. Firstly, we detected increase of phosphorylated mTOR at Ser2448, not Ser2481 in HG-treated cells compared to NG and MN control (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…It was reported that oxidative stress and ER stress pathways participate in Aldo-induced podocyte injury [18]. Notably, research shows that a cross talk exists between ER stress and the mammalian target of rapamycin (mTOR) signaling, another important signaling pathway that regulates cell survival [19, 20]. In podocytes, mTOR complex 2/Akt/NFκB-mediated activation of selective calcium ion channel protein TRPC6 involves in adriamycin-induced apoptosis [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among them is RPS6KB (p70)/p70-S6K (ribosomal protein S6 kinase B 70 kDa) which is phosphorylated at threonine 389 (T389) by MTORC1 10,18,20 . In turn, RPS6KB (p70) activates protein synthesis by promoting expression of ribosomal components, 21 and by phosphorylating translation initiation factors and components of the ribosomal machinery, including RPS6 (ribosomal protein S6) 19 . Little is known about PLK1′s role in the MTORC1 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…mTORC1 activates anabolic processes, including protein synthesis and inhibits catabolic processes such as autophagy, which safeguards the cell to maintain protein homoeostasis1357. mTORC1 exerts these effects by phosphorylating several substrates, including the kinases p70-S6K (ribosomal protein S6 kinase) and ULK1 (Unc-51-like kinase-1).…”
mentioning
confidence: 99%